2013
DOI: 10.1152/ajpendo.00471.2012
|View full text |Cite
|
Sign up to set email alerts
|

Gustducin couples fatty acid receptors to GLP-1 release in colon

Abstract: taste receptor subunits and ␣-gustducin found in enteroendocrine cells of the small intestine have been implicated in release of the incretin hormones glucagon-like peptide 1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP) in response to glucose and noncaloric sweeteners. ␣-Gustducin has also been found in colon, although its function there is unclear. We examined expression of ␣-gustducin, GLP-1, and GIP throughout the intestine. The number of ␣-gustducin-expressing cells and those coexpressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 99 publications
(152 reference statements)
1
31
0
Order By: Relevance
“…The decrease in octanoylated ghrelin secretion after feeding is partially induced by long-chain fatty acids that act directly on gastric GPR120-expressing ghrelin cells 32 . In addition, it was reported that the G protein α-gustducin is also involved in ghrelin octanoylation 31 and that α-gustducin could couple GPR120 33 . In our study, stearic acid, oleic acid, linoleic acid, and α-linolenic acid could have suppressed the release of octanoylated ghrelin via GPR120 and/or α-gustducin-mediated mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in octanoylated ghrelin secretion after feeding is partially induced by long-chain fatty acids that act directly on gastric GPR120-expressing ghrelin cells 32 . In addition, it was reported that the G protein α-gustducin is also involved in ghrelin octanoylation 31 and that α-gustducin could couple GPR120 33 . In our study, stearic acid, oleic acid, linoleic acid, and α-linolenic acid could have suppressed the release of octanoylated ghrelin via GPR120 and/or α-gustducin-mediated mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, individual FFA2- or FFA3-deficient mice showed low GLP-1 release in response to SCFAs, indicating that FFA3 is also involved in SCFA-evoked GLP-1 release [14,27]. High-dose (80 m M ) acetate-evoked GLP-1 releases were also observed in the isolated colonic mucosa from wild-type mice, but not from α-gustducin knockout mice [28]. As gustducin is a G i family member, the possibility was raised that G i -coupled FFA2 and/or FFA3 elicit GLP-1 releases in the colon.…”
Section: Possible Role Of Scfas In Glp-1 Secretionmentioning
confidence: 99%
“…Recently, both G protein α-subunits were found to be expressed in ghrelin-producing cells of the oxyntic glands of the stomach [12]. Numerous reports confirmed and extended the initial findings of taste-signaling elements in the GI tract to most regions of the Taste Receptor Gene Expression Outside the Gustatory System alimentary canal [2,4,16,17,23,108,117,122], with the colon harboring the highest number of α-gustducin-positive cells [123]. Noteworthy is the finding of a numerically important α-gustducin-expressing cell population confined to a relative restricted region of the stomach, the limiting ridge [112].…”
Section: Taste-signaling Components In the Gi Tractmentioning
confidence: 85%
“…Regarding the co-expression of taste transduction elements with taste receptors, it turned out that TRPM5-positive cells in mouse small intestine do neither express Tas1rs nor Tas2rs [2], while in the same regions α-gustducin exhibits a certain degree of colocalization with the Tas1r subunits [4,11,17]. Moreover, in the GI tract taste-related signaling elements may facilitate signal propagation of G protein-coupled receptors currently not considered as bona fide taste receptors such as fatty acid receptors and oleoylethanolamide and bile acid receptors which are co-expressed with α-gustducin in mouse colon [123].…”
Section: Taste-signaling Components In the Gi Tractmentioning
confidence: 99%
See 1 more Smart Citation